2014
DOI: 10.1103/physreve.89.062110
|View full text |Cite
|
Sign up to set email alerts
|

Local quenches with global effects in interacting quantum systems

Abstract: We study one-dimensional lattices of interacting spins-1/2 and show that the effects of quenching the amplitude of a local magnetic field applied to a single site of the lattice can be comparable to the effects of a global perturbation applied instantaneously to the entire system. Both quenches take the system to the chaotic domain, the energy distribution of the initial states approaches a Breit-Wigner shape, the fidelity (Loschmidt echo) decays exponentially, and thermalization becomes viable.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
196
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(219 citation statements)
references
References 92 publications
23
196
0
Order By: Relevance
“…We have shown that, while the former retains its power law structure even in the presence of a strong nonequilibrium perturbation the latter is a source of nonlinearity which generates locally an exponential decay in time of the OC correlator. Such a result appears to be consistent with a recent numerical study on Loschmidt echo decay in a 1D spin chain after a local quench starting from a highly excited state [59].We expect the physics of this quench-induced decoherence to be relevant in other contexts as well, most notably in steady-state transport, where it will result in a non-vanishing zero bias conductance in the weak-link limit as well as a non-zero backscattering correction in the dual limit [60], a result which is consistent with the non-vanishing impurity density of states recently found in [61].Acknowledgment -It is a pleasure to thank …”
supporting
confidence: 91%
“…We have shown that, while the former retains its power law structure even in the presence of a strong nonequilibrium perturbation the latter is a source of nonlinearity which generates locally an exponential decay in time of the OC correlator. Such a result appears to be consistent with a recent numerical study on Loschmidt echo decay in a 1D spin chain after a local quench starting from a highly excited state [59].We expect the physics of this quench-induced decoherence to be relevant in other contexts as well, most notably in steady-state transport, where it will result in a non-vanishing zero bias conductance in the weak-link limit as well as a non-zero backscattering correction in the dual limit [60], a result which is consistent with the non-vanishing impurity density of states recently found in [61].Acknowledgment -It is a pleasure to thank …”
supporting
confidence: 91%
“…Conclusion.-In general, the dynamics of initial states with energies very close to the edges of the spectrum is much slower than for states with energies closer to the middle of the spectrum [47]. Here, we showed that in an isolated system undergoing an ESQPT, a slow time evolution can occur also for initial states with energy very close to E ESQPT .…”
mentioning
confidence: 74%
“…For example, the energy width of the distribution determines the coefficient of the initial quadratic decay of L(t), as it can be seen by expanding e −iH f t in Eq. (3) to second order in t [46,48]. After a quench, a generic observable O has the following time evolution: …”
Section: Str-el] 15 Sep 2015mentioning
confidence: 99%
“…In the current era of non-equilibrium physics, it has been widely used as a model system to explore and exemplify non-equilibrium phenomena, including studies of the Loschmidt echo (e.g. [22,46,[64][65][66][67][68]), studies of quenches of the anisotropy parameter ∆ (e.g. [99,100]), and of quenches starting from a Néel state (e.g.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation